A Comparative Clinical Study Of Virechana And Vaitarana Basti With Trayodashanga Guggulu In Amavata with Special Reference To Rheumatoid Arthritis. - Shandilya, Vineet Kumar; Sharma, Ravi dutt; Rai, Girish Narain; Parida, Akhilanath; Swami, Deepali (International Research Journal of Ayurveda & Yoga, 2021)
The changing life style of human being by means of dietetic and behaviour pattern lays a major role in the manifestation of several disorders. This type of pattern may also lead to the development of the disease Amavata. Amavata has similarities with rheumatoid arthritis explained in allied sciences, Rheumatoid arthritis is a chronic multi system disease of unknown cause and characteristic feature of rheumatoid arthritis is persistent inflammatory synovitis , usually involving peripheral joints in a systemic distribution. Amavata is a disease having the predominance of Vata dosha , and also involvement of morbid Kapha and Amadosha. Hence a treatment which should alleviate morbid Vata, Pitta, Kapha is required in amavata. In Ayurvedic literature, a number of herbal preparations are described for the management of the disease. Vaitarana Basti is described in Chakradatta Niruhadikara section with its special indication in Amavata. Trayodashanga Guggulu Has Katu, Tikta Rasa, Ushna Virya And Vata-Kaphahara Properties. Bhavamishra has indicated it for Vatavyadhis, Asthi-Majja-Sandhi And Snayugata Vata. In this study The patients of group A were given Virechana by classical method followed by Trayodashanga guggulu for four weeks and Patients of group B were given Vaitarana Basti in the format of Kala Basti with Anuvasana of Shunthi Siddha Tila Taila for 16 days followed by Trayodashanga guggulu for four weeks. Results showed remarkable improvement in both groups proving Ayurveda treatment as a integral choice of treatment of amavata.